Kemampuan Pemecahan Masalah Calon Guru SD Ditinjau Dari Self Regulated Learning - Novianti Novianti; Asrul Karim; Jasmaniah Jasmaniah (Journal on Education, 2023)
The purpose of this study was to analyze the problem-solving abilities of prospective elementary school teachers in terms of self-regulated learning. The research was carried out at Almuslim University located in Bireuen, Aceh. The research subjects were 20 pre-service teacher elementary school. Data were collected from diagnostic tests and self-regulated learning attitude scales. The diagnostic test was given to 20 students consisted of two essay questions while the self-regulated scale consisted of five options, namely very often (SS), Often (S), KD (Sometimes), JR (Rarely), and TP (Never). The results showed that students who had high self-regulated learning were able to solve problem-solving skills well. Students who have moderate self-regulated learning have moderate solving abilities, this seems to be able to write mathematical models or be known from questions verbally or in written form, but without solving problems in the right way. Meanwhile, prospective elementary school teacher students who have low self-regulated learning indicate that they have low problem-solving skills. They understand the problem, but are unable to solve the problem properly. For that required the role of independent learning. Because the better the students' self-regulated learning, the better their mathematical problem solving abilities.Hence, it can be concluded that the student’ learning independence is at low level.